Vertical specialization and the quality of infrastructure - Hildegunn Kyvik Nordås (World Trade Organization (WTO), 2004)
This paper explores the role of producer services and ICT on international outsourcing. The motivation for outsourcing is to focus on core business and improve efficiency and outsourcing companies usually outsource a number of functions and the efficiency gains depend on the ability for the suppliers to deliver the required quality at the right time. If only one is late or delivers a substandard product, it will delay the entire process or reduce the quality of the final product. The timeliness of delivery and the fulfilment of quality standards depend critically on the availability of producer services. Transport, communication and other logistics services are obvious in this respect, but also services such as testing and technical services contribute to enable suppliers in low-cost countries to enter the outsourcing market. I therefore argue that international outsourcing can best be understood within an analysis framework of many suppliers that are interdependent, and the O-ring theory of production is such a theory. The paper first presents and modifies this model and then explores its predictions in an empirical analysis of the determinants of international vertical specialization as defined by an index developed by Hummels et al. (2001). The index is calculated for a cross-section of 52 countries and 5 sectors and regressed on a number of variables affecting the timeliness of delivery. It is found that vertical specialization is sensitive to trade barriers and infrastructure quality and cost of infrastructural services. The relative importance of trade barriers and various indicators of infrastructure vary between sectors. Vertical specialization in the electronics sector appears to be most sensitive to trade barriers and the density of the telecommunication network. This is also the case for the motor vehicles sector, but the size of the parameters is somewhat lower. The chemicals sector is most sensitive to the restriction on maritime services, while for textiles and clothing the aggregated measure of infrastructure had the highest explanatory power. Only in the electronics sector did the wage level (GDP per capita was used as a proxy) matter for vertical specialization.
Keywords: F12; F14; 330; O-ring theory of production; International trade; Vertical specialization